Fictions of the “As Not”: Messianic vocations of the common for a world beyond work and aesthetics - Vindel, Jaime (Re-visiones, 2024)
This text traces the survival of St Paul messianism at various different landmarks in political philosophy, social activism and contemporary art practices. It takes the critical reconsideration of the concept of class as its starting point, showing us how it left behind the egalitarian universalism of the radical and interracial policy of early modernity (the transoceanic proletariat) to become a stable and discriminatory identity (the national working classes) designed to address the conflict between capital and labour. From this perspective, the second part of the article analyses the way in which recent social movements, inspired by the operaista rejection of Fordist work, are trying to go beyond the structural configuration of modern experience in which work and aesthetics have a key function.